Zwangsmaßnahmen in deutschen Kliniken für Psychiatrie und Psychotherapie: eine Pilotstudie der DGPPN zur Erprobung eines einheitlichen Erfassungsinstrumentes = Coercive measures in German hospitals for psychiatry and psychotherapy : a pilot study by the DGPPN to evaluate a uniform assessment instrument - Adorjan, Krisztina; Herpertz, Sabine; Häfner, Sibylle (Der Nervenarzt, 2017)
Study objectiveA simple instrument to record case-related coercive measures was tested as part of a pilot project of the German Association for Psychiatry, Psychotherapy and Psychosomatics (DGPPN).MethodsTo assess coercive measures data were collected for 3 months in 8 German hospitals for psychiatry and psychotherapy. The type of measures used, the main diagnosis and the legal basis for the coercive measures were documented.ResultsIn the sample studied, coercive measures were applied in 8% of cases. Coercive measures were most commonly used in patients with a schizophrenic disorder. The principle of justifiable necessity according to § 34 of the German Penal Code was used particularly often as the legal basis for justifying the coercive measures.ConclusionSuitable measurement instruments and reliable data that enable the learning of best practices represent the basis for a reduction of coercive measures.